The different paths of Buddhism : a narrative-historical introduction - Olson, Carl (Rutgers University Press, 2005)
"Offers a comprehensive introduction to the main branches of the Buddhist tradition in both the Mahayana and Theravada schools, including the Madhyamika school, the Yogacara school, Pure Land devotionalism, Tibetan Tantric Buddhism, Zen Buddhism, and village folk Buddhist traditions. Chapters explore the life and teachings of the Buddha in historical context, the early development and institutionalization of Buddhism, its geographic spread across Asia and eventually to the United States, philosophy and ethics, the relationship between monks and laity, political and ethical implications, the role of women in the Buddhist tradition, and contemporary reinterpretations of Buddhism."--Page 4 of cover